2007
DOI: 10.1111/j.1526-4610.2007.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Yoga Therapy in the Treatment of Migraine Without Aura: A Randomized Controlled Trial

Abstract: Background.-Numerous studies have explored the effectiveness of complementary and alternative medicine in the treatment of migraine but there is no documented investigation of the effectiveness of yoga therapy for migraine management.Objectives.-To investigate the effectiveness of holistic approach of yoga therapy for migraine treatment compared to self-care.Design.-A randomized controlled trial. Methods.-Seventy-two patients with migraine without aura were randomly assigned to yoga therapy or selfcare group f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
1
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 26 publications
2
153
1
11
Order By: Relevance
“…Outcomes differed across studies, but included headache symptoms and related disability [20,[33][34] as well as perceptions of self-efficacy [35] and selfmanagement behaviors [36]. Of the studies examining headache symptoms and disability, two report significant treatment effects [33][34]. One study notes a trend favoring treatment [35], and the other shows no comparative benefit of treatment [20], but data were reported on only 30 participants and the analyses were likely underpowered.…”
Section: Self-management Class III Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Outcomes differed across studies, but included headache symptoms and related disability [20,[33][34] as well as perceptions of self-efficacy [35] and selfmanagement behaviors [36]. Of the studies examining headache symptoms and disability, two report significant treatment effects [33][34]. One study notes a trend favoring treatment [35], and the other shows no comparative benefit of treatment [20], but data were reported on only 30 participants and the analyses were likely underpowered.…”
Section: Self-management Class III Evidencementioning
confidence: 99%
“…The remaining five studies examined self-management interventions for headaches [20,[33][34][35][36]. Treatments included an Internet-based self-help program with therapist-initiated telephone contacts [20], videotape training intended to promote self-efficacy [36], an Internet-based education program [33], yoga [34], and home-based training by lay providers with migraine [35].…”
Section: Self-management Class III Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The use of complementary and alternative medicine (CAM) in migraine is a growing phenomenon which, though increasingly widespread, is poorly understood. [27][28][29] Ayurveda is a traditional medical system used by a majority of India's 1.1 billion population. 30 Though Ayurvedic therapy is popular among migraine sufferers, there are very few studies which have compared pharmacotherapy pertaining to combination of two lines of treatment aiming for the holistic view of treatment with aim of increasing compliance ,increasing potency of drugs and reducing side effects caused by allopathic medicines when administered alone.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced pain and disability and increased quality of life have been reported in RCTs of yoga for various conditions in adults, including migraines and headaches [42,43], rheumatoid arthritis [44], osteoarthritis [45] and chronic low back pain [46]. A review of the literature on yoga for cancer [47] concluded that yoga interventions consistently yield modest improvements across a range of outcomes, including psychological (mood, distress, stress) and somatic (e.g., sleep disturbance) symptoms.…”
Section: Introductionmentioning
confidence: 99%